Model Kirkpatrick Dalam Evaluasi Program Pelatihan Kepemimpinan Tingkat IV - Alamsyahril (Cendekia Niaga, 2020)
After organizing training, it is necessary to evaluate the training program because the results of the evaluation will provide feedback for the improvement of the next training program. In this evaluation research we identified the effectiveness of the Leadership Training Program for supervisory officials organized by the Staffing and Human Resources Development Agency. The Kirkpatrick’s model was used to identify reaction, learning, behavior, and results. The analysis using this model state that the participants have shown positive reactions to lecturers and coaches, the learning process has shown the success of the distribution of the value of the graduation of participants in which most of participants graduated with satisfactory qualifications, and there were some behavior changes of Leadership Training alumni. They stated that the training can support the implementation of their papers in the mid and long term.